Simulation model of PID for DC-DC converter by using MATLAB - Salam Waley Shneen; Dina Harith Shaker; Fatin Nabeel Abdullah (International Journal of Electrical and Computer Engineering (IJECE), 2021)
The change in loads in most applications whose source of nutrition is a renewable energy system. Renewable energy systems can change according to climatic conditions. To control and control these changes, the use of conventional control systems such as PIDs. The PID is one of the most common and used conventional control systems that have been chosen to output the type of power electronic devise (DC-DC converter) in different working conditions. The current study aims to improve the system performance through simulation. Simulation results demonstrate the effectiveness of the system with the controller based on setting parameters such as recording system states, embedded elevation time and transient response.